The Impact of Rural-Urban Migration on Subjective Well-Being in South Africa. Issue 9 (1st September 2016) - Mulcahy, Kirsten; Kollamparambil, Umakrishnan
Abstract: This paper quantifies the short to medium term impact of rural-urban migration on an individual's subjective well-being in South Africa between 2008 and 2012. We work through different econometric specifications; using instrumental variables to control for endogeneity caused by shock-induced self-selection, and Propensity Score Matching to control for migration self-selection bias. We find that rural-urban migration leads to a decrease in subjective well-being by 8.3 per cent. We suspect that the decreased well-being is a result of false expectations and changing relative groups used to peg aspirations, as well as the emotional cost of being away from family and a home environment.